Fermented bed flooring systems enhance profitability in smallholder native pig production - Sivilai, Bounlerth; Vongpaserth, Thonglai; Liang, Juan Boo; Bush, Russell (CSIRO, 2024)
Context. Traditional smallholder pig farming plays an important role in farmers’ income and national food security in the low- and middle-income countries in Southeast Asia including Laos; however, its productivity is low and it is often environmentally unsustainable. Aims. The objectives of this study were to evaluate the effects of using fermented bed-floor housing compared with the conventional concrete-floor housing on growth, carcass treats and economic return on raising Laos native pigs. Methods. The study was conducted at the Faculty of Agriculture, National University of Laos. Twenty four castrated native pigs, aged ±3 months with initial liveweight of 17 ± 2 kg/head, were randomly assigned to the following housing types as treatments: (1) conventional concrete-floor system (CS) as control, and (2) fermented bed-flooring system (FB). The pigs were fed with similar diet with 16.01% crude protein and 11,796 kJ/kg gross energy for a period of 84 days after a 14-day adaptation to the feed. Each treatment was replicated four times (pens), with three pigs/pen. Data on feed intake, liveweight change, carcass trait and costs and returns of production in the two treatments were analysed using Student’s paired-sample t-test. Key results. Pigs kept in FB flooring had higher DM and nutrient (crude protein, crude fibre, ether extract and organic matter) intakes than did their counterparts raised in the CS, but the differences were not significant when adjusted to bodyweight basis. There were also no significant differences in growth performance (average daily gain (ADG) and feed conversion ratio (FCR)), and carcass traits, except that pigs from FB had higher hot carcass weight, dressing percentage and rib and bone weights. Native pigs kept in the FB system had significantly higher total production costs because of the cost of the bedding material, but also had four-fold higher net income return generated from the sale of the fermented floor compost. Conclusions. Fermented bed-flooring system has no significant impact on growth and key carcass traits, but significantly enhanced profit. Implications. Fermented bed-flooring system should be promoted for rearing local pigs under smallholder farms to increase profit and protect the environment in the low- and middle-income countries. © 2024 The Author(s) (or their employer(s)). Published by CSIRO Publishing.